THE EFFECT OF MOTIVATION ON THE PERFORMANCE OF EMPLOYEES OF PT. TELKOM PROPERTY AREA VII KTI - Jam'an, Jam'an; Musdalifah, Eva; Syafaruddin, Syafaruddin (Perpustakaan dan Penerbitan Unismuh Makassar, 2018)
This research was conducted at PT. Telkom Property Area VII KTI, the research population was all employees of PT. Telkom Property Area VII KTI and as many as 24 employees while the sample size was determined using the slovin method as many as 24 sample employees. Data collection uses observation techniques, questionnaires, while data analysis uses validity tests, reliability tests, simple linear regression tests, coefficients of determination, and hypothesis testing using partial significance tests (t statistical test). The results of data analysis show that the motivation variable with employee performance at PT. Telkom Property Area VII KTI, which is indicated by the validity test is greater than r_table 0.423 (valid), the reliability test obtained Cronbach's Alpha value is greater than r_table (Cronbach's Alpha 0.738 > r_tabel 0.423), simple linear regression test Y = a+bX or (Y = 10.026 + 0.964X) (positive value), the coefficient of determination is 0.788, while for hypothesis testing the value of t_count is greater than t_table (t_count 9.056 > t_table 2.068) at level significant 5%. The result of determination obtained a coefficient of determination of 0.788 which means that 78.8% of the independent variable (X) explains the dependent variable (Y) or in other words, the independent variable (X) on the rise and fall of employee performance (Y) is 78.8% while the rest 21.2% was influenced by other variables that were not included in this study.